Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x - 7 = 7
x = 7 + 7 = 14
b) 2x - 7 = 17
2x = 17 + 7 = 24
x = 24/2 = 12
c) 2/x +7 = 8
2/x = 8 - 7 = 1
x = 2/1 = 2
d) (x + 74) - 318 = 200
x + 74 = 200 + 318
x + 74 = 518
x = 518 - 74 = 444
e) 3636/(12x - 91) = 36
12x - 91 = 3636/36
12x - 91 = 101
12x = 101 + 91 = 192
x = 192/12 = 16
a) x-7=17
x=17+7
x=24
b) 2x-7=17
2x=17+7
2x=24
x=24:2
x=12
c) 2:x+7=8
2:x=8-7
2:x=1
x=2:1
x=2
d) (x+74)-318=200
x+74=200+318
x+74=518
x=518-74
x=444
e) 3636:(12x-91)=36
12x-91=3636:36
12x-91=101
12x=101+91
12x=192
x=192:12
x=16
\(\left(3x-4\right)\left(x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}3x-4=0\\x-1=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}3x-4=0\Rightarrow3x=4\Rightarrow x=\frac{4}{3}\\x-1=0\Rightarrow x=1\end{cases}}\)
Vậy x bằng \(\frac{4}{3}\) và x = 1
\(\left(3x-4\right)\left(x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{4}{3}\\x=1\end{cases}}\)
a.8x+28-9x+6=24
<=> -x+34=24
<=> -x=24-34
<=> x=10
b. 3-6x-x-18=7
<=> -7x=7+18-3
<=> -7x=22
<=> x=22/-7
-2x - ( x - 17 ) = 34 - ( -x + 25 )
-2x - x + 17 = 34 + x - 25
-3x + 17 = 34 - 25 + x
-3x + 17 = 9 + x
-3x -x = 9 - 17
-4x = -8
=> 4x = 8
x = 8 : 4
x = 2
Vậy x = 2
-2x-(x-17)=34-(-x+25)
<=>-2x-x+17=34+x-25
<=>-2x-x-x=-17+34-25
<=>-4x=-8
<=>x=2
vậy x=2
2x - 7 = 17 - x
2x - x = 17 - 7
1x = 10
=> x = 10
x = 8 nha bạn